In situ determination of creep properties of sea ice with the pressuremeter - Murat, J. R.; Ladanyi, B.; Huneault, P. (Canadian Geotechnical Journal, 1989)
A series of pressuremeter creep and relaxation tests was carried out in the spring of 1987 in a sea-ice cover at Igloolik, Northwest Territories, for the purpose of testing some new procedures for in situ determination of creep properties of sea ice. Compared with a similar field study carried out 9 years earlier, the present investigation included some clear improvements, not only in the instrumentation and data acquisition system but also in the data interpretation and processing. In particular, it is shown that consistent values of creep parameters can be obtained only if proper consideration is made of the amount of stress redistribution taking place before and during each new load application. Key words: in situ testing, pressuremeter, sea ice, creep properties, stress redistribution.